ANALISIS KUALITAS PELAYANAN PEMBUATAN SURAT IJIN USAHA PERDAGANGAN DI KANTOR BADAN PELAYANAN PERIJINAN TERPADU (BPPT) KOTA SEMARANG - Reinaldi, Didi Hadiyanto; Dwimawanti, Ida Hayu; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2013)
Manufacturing services permit trading is a form of public service provided by the local government to the public and regulated by Regulation No. 6 of 2009. Permit trading is to control any activity that causes interference place of business, hazards, losses from time to time, so as not to interfere with the preservation of the business and harm society. This study aims to analyze quality of service to manufacturing trade business license granted to prospective entrepreneurs in the Integrated Licensing Service Agency (BPPT) Semarang.This study used a qualitative descriptive method. The locus of this study in the office of the Integrated Licensing Service Agency (BPPT) of Semarang and the focus Making Service Quality Trading Business License. The data source using the primary data source and secondary data. The research instrument uses the researcher as research instrument, interview guide, informer. Technique selection study using purposive sample of informants. Techniques of data collection through interviews, observation, documentation and literature. Data analysis techniques using domain data analysis techniques.In this study there were 5 observed phenomenon that service procedures, clarity attendant service, speed of service, the reasonableness of the cost of services, as well as the certainty of the service charge. From the results obtained clarity and reasonableness of service personnel has found that the cost of servicing a good result. As for the procedure of service, speed of service and assurance services necessary costs of particular concern because it is considered less than the maximum.